Effects of Online Nutrition Training Program About Mediterranean Diet on Anthropometric Measurements and Diet Quality in Overweight and Obese Adolescent Girls - Kabaran, Seray; Memis, Tugce (Marmara Univ, Inst Health Sciences, 2023)
Objective: This study was conducted to evaluate the effect of an online nutrition training program about the Mediterranean diet for 8 weeks in overweight and obese female high school students on anthropometric measurements and diet quality. Methods: A total of 86 students between the ages of 14-18 years were included in the study, and they were divided into two groups as nutrition training (n=44) and control groups (n=42). The Mediterranean Diet Quality Index (KIDMED) scores were calculated and anthropometric measurements of groups were taken by the dietician at the beginning and at the end of the study. Results: The KIDMED score of the nutrition training group was 4.59 +/- 2.40 at the beginning, later on it increased to 7.43 +/- 2.57 after the program (p= .001). After the program, it was determined that the difference between the KIDMED scores of the nutrition training and control groups were statistically significant (p= .034), however the decrease in body weight (p= .09), BMI (p= .64), and waist circumference (p= .06) were similar between groups. Conclusion: As a result of the study, it can be said that online nutrition training program about the Mediterranean diet for 8 weeks may affect the diet quality positively of overweight and obese female adolescents, but long-term programs should be planned to determine the effects on anthropometric measurements.
Keywords: Adolescent; anthropometry; diet; mediterranean diet; obesity